A simple technique for repositioning of the mandible by a surgical guide prepared using a three-dimensional model after segmental mandibulectomy - Akinori Funayama; Taku Kojima; Michiko Yoshizawa; Toshihiko Mikami; Shohei Kanemaru; Kanae Niimi; Yohei Oda; Yusuke Kato; Tadaharu Kobayashi (SpringerOpen, 2017)
Abstract Background Mandibular reconstruction is performed after segmental mandibulectomy, and precise repositioning of the condylar head in the temporomandibular fossa is essential for maintaining preoperative occlusion. Methods In cases without involvement of soft tissue around the mandibular bone, the autopolymer resin in a soft state is pressed against the lower border of the mandible and buccal and lingual sides of the 3D model on the excised side. After hardening, it is shaved with a carbide bar to make the proximal and distal parts parallel to the resected surface in order to determine the direction of mandibular resection. On the other hand, in cases that require resection of soft tissue around the mandible such as cases of a malignant tumor, right and left mandibular rami of the 3D model are connected with the autopolymer resin to keep the preoperative position between proximal and distal segments before surgical simulation. The device is made to fit the lower border of the anterior mandible and the posterior border of the mandibular ramus. The device has a U-shaped handle so that adaptation of the device will not interfere with the soft tissue to be removed and has holes to be fixed on the mandible with screws. Results We successfully performed the planned accurate segmental mandibulectomy and the precise repositioning of the condylar head by the device. Conclusions The present technique and device that we developed proved to be simple and useful for restoring the preoperative condylar head positioning in the temporomandibular fossa and the precise resection of the mandible.